2022
DOI: 10.3390/ma16010075
|View full text |Cite
|
Sign up to set email alerts
|

The Magnetic Properties and Magnetocaloric Effect of Pr0.7Sr0.3MnO3 Thin Film Grown on SrTiO3 Substrate

Abstract: The magnetic behaviors and magnetocaloric effect (MCE) of Pr0.7Sr0.3MnO3 (PSMO-7) film grown on a (001) SrTiO3 single-crystal substrate by a pulsed laser deposition (PLD) were studied in this paper. X-ray diffraction with a high resolution (HRXRD) measurement shows that PSMO-7 film is grown with a (001) single orientation. The magnetic properties and the MCE related to the ferromagnetic (FM) phase transition of the PSMO-7 film are investigated using the temperature dependence of magnetization M(T) and the magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…In this case, the film-substrate interface may emulate an apparently emergent FM response caused by pinning local magnetic moments induced by the excitation magnetic field [ 38 ]. This weak FM character, prolonging above 100 K, hinders the application of a Curie-Weiss model [ 6 ]. The previous results agree with those reported in Lu-doped EuMnO 3 thin films [ 17 , 39 ]; however, irreversibility behavior seems more marked in these samples.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, the film-substrate interface may emulate an apparently emergent FM response caused by pinning local magnetic moments induced by the excitation magnetic field [ 38 ]. This weak FM character, prolonging above 100 K, hinders the application of a Curie-Weiss model [ 6 ]. The previous results agree with those reported in Lu-doped EuMnO 3 thin films [ 17 , 39 ]; however, irreversibility behavior seems more marked in these samples.…”
Section: Resultsmentioning
confidence: 99%
“…Rare-earth manganites R MnO 3 are among some of the most relevant functional oxide materials, mainly due to intrinsic strong correlated electron mechanisms, leading to exhibiting structural-orbital-magnetic-electric coupling effects. In particular, it can be used for barriers and interfaces in controlled spin transport devices [ 1 , 2 , 3 , 4 , 5 , 6 ]. According to the ionic radius of rare earth elements, the manganites can exhibit two main distinct structural symmetries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hope these inferences provide clues for the advancement of theories in the field of MCE to enable the engineering of materials for magnetic refrigeration at room temperature (see, for instance, Ref. [31] for a report on thin film route of a manganite to enhance MCE with respect to Gd metal at room temperature). This entropy behavior of the Er compound meets the much-needed [27] characteristic of "reversibility" for magnetocaloric applications in the low temperature range.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, a promising nanostructured LSMO polycrystalline film grown on quartz with greater LFMR (31%), CMR (56%) and sensitivity (0.28 V/T at B = 0.25 T) was fabricated and suggested by Stankevic et al for CMR sensors [2]. Bojun et al reported the fabrication of PSMO films, growing on SrTiO 3 films, with the potential for magnetic refrigeration application [15]. However, such studies with LSMO deposition on corning glass (CG) were halted after 2014 due to their amorphous natures [7,16,17].…”
Section: Introductionmentioning
confidence: 99%